Understanding and Attitudes of University Students towards Plagiarism in Academic Writing at the University - Safitri, Diya; Arsyad, Safnil (Journal of English for Specific Purposes in Indonesia, 2022)
In the academic world, plagiarism is prone to be occured. Academic dishonesty has emerged as a major concern and difficulty for the educational system. The goal of this research is to find out the understanding and attitudes of students towards plagiarism in academic writing. This research used of descriptive quantitative research methods with a questionnaire instrument. Based on the results, understanding of students obtained, namely strongly agree as many as 42.6%, agree as many as 43.7%, disagree as many as 4.2%, and strongly disagree as many as 1.6%. While, based on the results of students' attitudes towards plagiarism as a whole obtained, namely strongly agree as many as 37.9%, agree as many as 51.2%, disagree 6.3%, and strongly disagree as many as 4.6%. So, the attitude of students at the university shows a good attitude towards academic writing at the university. The students are quite familiar with the basic concepts of plagiarism but still cannot apply them correctly and appropriately. With this study, it is hoped that students will become more open and understand the concept of understanding plagiarism and what behaviors can be indicated as plagiarism behavior.